Valuation method of intellectual property pledge financing based on income interval analysis and risk adjustment coefficient - Rengang Su; Ming Li; YinHai Fang; Chonghuai Yang (Humanities & Social Sciences Communications, 2023)
Abstract This study has developed a new method to valuate intellectual property for pledge financing. First, based on interval theory and the relevant calculation rules, the income interval model is and then used to calculate the interval values of intellectual property. Second, based on the change structure of risk indicators, the AHP and set-valued statistics are utilized to calculate the risk adjustment coefficient. Third, the point value of intellectual property is calculated with its values at an interval scale and risk adjustment coefficient. The values of intellectual property at an interval scale provide the two parties negotiating pledge financing with a reference range of loan amounts. The risk adjustment coefficient becomes a crucial indicator for measuring value evaluation risk. The point value of intellectual property specifies how much the bank loan amount can deviate from the values of intellectual property at an interval scale. The method creates a multi-indicator system to valuate intellectual property for pledge financing, which lowers the risk of intellectual property pledge financing to a significant extent and facilitates its operation. Moreover, the method has been proven to be efficient in practice.